Can elementary school students really benefit from using video games at school? - JULIEN BUGMANN (Metaichmio Publications, 2018)
Can playing video games improve expected learning outcomes for elementary school students? To address this question, we examined relationships between the knowledge and competencies that students developed through video gaming and the common core of knowledge and skills covered in France's education competency framework. We used an experimental design to investigate elementary school students who played a serious video game. The results reveal associations between playing Food Force and the key competencies described in the competency framework, and more particularly, that this type of serious gaming can help students develop these key competencies.